Physical fitness profile in college students who follow weight training: Yo-yo intermittent test level 1 - Saputra, Eko; Putra, Martinez Edison; Rianto, Louis; Tjahyanto, Teddy; Widiyati, Restu; Aziz, Ishak (Universitas Tanjungpura, 2023)
This study aims to determine the physical fitness of sports students who take part in fitness activities. This study uses a quantitative descriptive approach with a survey method, which in this study carried out tests and measurements of level 1 intermittent yo-yo tests. The population is sports students who are actively doing fitness activities on campus 3 of sports science, Tanjungpura University. The sampling technique used purposive sampling in order to obtain 13 students as samples. Analysis of percentage descriptive data with the help of Microsoft Excel 2013 software. This result can be seen from the percentage which shows 15% in the good category, 15% in the bad category and 70% in the medium category. The conclusion of this study is that the physical fitness of sports students who take part in fitness is in the moderate category, the results show that the activities carried out can have a positive impact on physical fitness